Explaining Malaysian bilateral trade with OIC members - Ismail, Normaz Wana; Said, Rusmawati (2010)
This paper examine the bilateral export between Malaysia and 52 OIC members for the period of 1990 to 2006.Using a traditional gravity-equation framework, this study investigate to what extent export creation between Malaysia and the OIC members after being long term membership since 1969. The major finding is that the market size of members is important determinant for Malaysian trade. Furthermore, there is evidence Malaysia trade with high income economies more than other members. Empirical result also support that trade increases between Malaysia and OIC member if they are not similar in term of size and factor endowments.